Investigtion and Scientific Explanations of Superstitious Beliefs Held By Senior School Science Students of Oyo State, Nigeria - AHMED, Mulkah Adebisi; Oyedibu, Mary Oyepeju (Perspektif Pendidikan dan Keguruan, 2022)
This study identified the superstitious beliefs held by the senior school science students of Afijio, Oyo State, Nigeria. Scientific explanations and educational implications of the identified superstitious beliefs were investigated. Purposive random sampling technique was employed to select 300 S.S. 2 students based on socio-economic background. The responses received formed data for the analysis. The Biology-related Superstitious Beliefs Questionnaire (BSBQ) was the instrument. Four research questions were raised and answered while one hypothesis was formulated and tested. The data collected were subjected to frequency count, percentage, ranking and t test. The results indicated that the respondents (i) held some superstitious beliefs about health, pregnancy, food and animals. (ii) A good number of the superstitious beliefs were found to have scientific explanations while some do not have. (iii) Superstitious beliefs affect students in classroom situations (iv) students from poor homes held more superstitious beliefs than those from rich home but there was no statistical difference between them. The recommendation made are that (i) Science educators should relate science more closely to learners, (ii) provide scientific explanations to superstitious beliefs and (iii) Government and non-governmental organizations should support in eradicating superstitious beliefs in our schools irrespective of students socio-economic background.